2021
DOI: 10.1155/2021/3980872
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone-Induced Neutropenia in a Schizophrenic Patient: A Case Report and Literature Review

Abstract: Neutropenia is an adverse effect of various pharmacological therapies, including antipsychotics. Among the second-generation antipsychotic (SGA) medications, clozapine is most notable for neutropenic adverse effect. Risperidone, another SGA drug, is linked mainly with metabolic adverse effects, but rarely, blood dyscrasia adverse reactions have been reported. Hence, we report the case of a 56-year-old African American woman who developed severe neutropenia following two weeks of oral risperidone treatment. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…More recently, Atolagbe et al reported the case of a 56-year-old African American female who experienced a significant drop in her neutrophil count after taking oral risperidone for two weeks. Her neutrophil levels returned to the normal range when she stopped taking risperidone and switched to haloperidol [21].…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…More recently, Atolagbe et al reported the case of a 56-year-old African American female who experienced a significant drop in her neutrophil count after taking oral risperidone for two weeks. Her neutrophil levels returned to the normal range when she stopped taking risperidone and switched to haloperidol [21].…”
mentioning
confidence: 94%
“…A literature search was done on PubMed database (MeSH terms: risperidone, leukopenia and/or neutropenia ) for available evidence on management of risperidone-induced leukopenia and/or neutropenia either with rechallenging or not includes 18 case reports of risperidone-induced leukoneutropenia as shown in the ▶Table 1 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The mean age was 44.06 (range: 7 to 90 years old).…”
mentioning
confidence: 99%
See 1 more Smart Citation